Analisis Perbandingan Kinerja Keuangan dan Tingkat Kesehatan Bank Sebelum dan Sesudah Merger dan Akuisisi Pada Perbankan - Salsabila, Adhila Yasmin; Rokhmawati, Andewi; Fiona (SAFE-Network, 2025)
This study aims to determine the comparison of financial performance and bank health levels before and after mergers and acquisitions in the banking sector. The sample in this study consisted of seven banks. The data used in this study was secondary data, namely banking financial reports published by the Indonesia Stock Exchange. The data analysis techniques used in this study are the Shapiro Wilk normality test and hypothesis testing using the parametric independent sample t-test and non-parametric Mann-Whitney U test with the help of the SPSS 27 calculation application. The results of this study indicate that there is a significant effect of the merger and acquisition process on the Capital Adequacy Ratio (CAR) and Loan to Deposit (LDR), between before and after the merger and acquisition. However, there is no significant effect of the merger and acquisition process on Non-Performing Loans (NPL), Return on Assets (ROA), Net Interest Margin (NIM), and Good Corporate Governance (GCG) between before and after the merger and acquisition. In general, mergers and acquisitions have not yet provided synergies for banks that have undergone mergers and acquisitions.